O Noise in the context of intensive care: contribution to safety and quality of care - descriptive study - Marcelo, Idália de Jesus Gavino Baleizão (2022)
Introduction: Excessive noise in hospitals negatively affects patients’ sleep and recovery, causes stress and fatigue in the team and makes communication difficult. The 1999 World Health Organization (WHO) guidelines for community noise recommend a maximum of 35 dBA at night and 40 dBA during the day for hospital environments. The increasing technological complexity, new information and consequent increase of health care complexity, made it imperative to work on the patient’s safety culture in order to implement preventive actions and improve the quality of the care provided. Methods: This is a quantitative study, with a descriptive, cross-sectional observational approach and a non-probabilistic sampling method. Objective: The general objective is to assess the level of noise to which nurses in an ICU are exposed for approximately 48 hours. In a first phase we will evaluate the noise level with a sound level meter and in another, characterized the individual perception, through the application of a questionnaire. Results: The values observed with regard to the mean daily noise intensity, evaluated in this study, were approximately 55 dBA for daytime periods and 50 dBA for nighttime periods, with maximum peak values of 83.7 dBA, higher values recommended by international organizations. On the other hand, health professionals are aware of the presence of noise in their workplaces. Conclusion: Given the results obtained, although WHO and US EPA guidelines are likely to be unachievable in any critical care area of a hospital, we consider that reducing some of these elevated levels should be possible after identifying and locating primary sources and define prevention and control measures in order to minimize or eliminate the emission of noise.